Optical element having compressive stress layer

CN116018531BActive Publication Date: 2026-10-09OHARA INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202180053882.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-19
Filing Date
2021-10-04
Publication Date
2026-10-09
Estimated Expiration
2041-10-04

AI Technical Summary

Technical Problem

[0008]另一方面,在摄像光学系统设备中,存在光学元件和光学设备整体因日光直射而被急剧加热,在加热后因雨等或洗车时的水而被急剧冷却因而光学元件产生破裂的技术问题

Benefits of technology

[0013] The technical problem that the invention aims to solve

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004102766240000091
    Figure BDA0004102766240000091
  • Figure BDA0004102766240000101
    Figure BDA0004102766240000101
  • Figure BDA0004102766240000111
    Figure BDA0004102766240000111
Patent Text Reader

Abstract

The present invention provides an optical element having excellent press formability, a desired compressive stress and depth of the compressive layer, and excellent thermal shock resistance. The optical element has a compressive stress layer on a surface, the compressive stress of the compressive stress layer is 100 to 1000 MPa, the depth of the compressive stress layer is 10 to 100 μm, and the temperature at logη = 8.5 (viscosity) is less than 700°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an optical element having a compressive stress layer. Background Technology

[0002] In recent years, the demand for projection optical system equipment such as projectors or video optical system equipment such as vehicle-mounted cameras and surveillance cameras has increased. For optical components used inside optical systems, it is also necessary to consider countermeasures for various environments.

[0003] In projection optical system equipment, in order to project images onto the screen more clearly, a high-power semiconductor light source is required. In the past, high-voltage discharge and other methods were used, but due to the need for compactness, LD or LED light sources have begun to be used.

[0004] Because heat is released along with light from the LD and LED light sources in the projection optics system, the optical components inside the system are also exposed to high temperatures. In particular, the use of high-power light sources exposes the system to significant temperature variations. These variations are substantial, with the temperature of the optical components potentially reaching over 200°C, posing a technical problem of potential breakage when the temperature is reduced from this high temperature to room temperature.

[0005] Therefore, the optical elements used in projection optical systems not only need to have high transmission and high homogeneity, but also need to be resistant to thermal shock.

[0006] In addition, the optical elements inside the projection optical system equipment need to be made into aspherical lenses with complex shapes that are arranged in a matrix, requiring higher molding properties than previous optical elements.

[0007] In particular, since the production of aspherical lenses by grinding and polishing is costly and inefficient, precision molding, which involves heating and softening a preform material obtained by cutting or grinding a glass blank or glass block, and then pressing the preform material with a high-precision mold, can eliminate the grinding and polishing steps and achieve low-cost, mass production.

[0008] On the other hand, in camera optical system equipment, there is a technical problem that the optical elements and the optical equipment as a whole are rapidly heated by direct sunlight, and then rapidly cooled by rain or water during car washing, causing the optical elements to crack.

[0009] As a glass with good pressing and forming properties, the invention described in Patent Document 1 has been disclosed.

[0010] Existing technical documents

[0011] Patent documents

[0012] Patent Document 1: Japanese Patent Application Publication No. 2019-006643 Summary of the Invention

[0013] The technical problem that the invention aims to solve

[0014] However, in the invention disclosed in Patent Document 1, although glass with good compressibility can be obtained by lowering the transfer point, the temperature at logη = 8.5 is too high, so it is impossible to manufacture complex aspherical lenses, and thus it is difficult to stabilize the thermal shock resistance.

[0015] The present invention was made in view of the above-mentioned technical problems, and its purpose is to obtain an optical element with excellent compressive stress and compressive stress layer depth, and excellent thermal shock resistance.

[0016] Methods for solving technical problems

[0017] In order to solve the above-mentioned technical problems, the inventors conducted in-depth experimental research and completed the following invention: by making the temperature at logη = 8.5 (viscosity) less than 700°C, the compressibility can be improved, and it has a compressive stress of 100-1000 MPa and a compressive stress layer depth of 10-100 μm. Moreover, the ratio of compressive stress to thermal stress (compressive stress / thermal stress) is 1.00 or more, thus exhibiting excellent thermal shock resistance.

[0018] (1) An optical element having a compressive stress layer on its surface, wherein...

[0019] The compressive stress of the compressive stress layer is 100–1000 MPa, and the depth of the compressive stress layer is 10–100 μm.

[0020] The temperature at which logη = 8.5 (viscosity) is less than 700℃.

[0021] (2) The optical element as described in (1), wherein the refractive index (nd) is 1.45000 or more and 1.70000 or less, and the Abbe number (νd) is 45.00 or more and 70.00 or less.

[0022] (3) The optical element as described in (1) or (2), wherein the ratio of compressive stress to thermal stress (compressive stress / thermal stress) is 1.00 or more.

[0023] (4) The optical element as described in any one of (1) to (3), wherein the optical element can be used in a projection optical system device.

[0024] (5) The optical element as described in any one of (1) to (3), wherein the optical element can be used in photographic optical system equipment. Detailed Implementation

[0025] The optical element of the present invention has a compressive stress layer on its surface. Methods for forming the compressive stress layer on the surface include physical strengthening and chemical strengthening methods; the optical element of the present invention can be formed by chemical strengthening.

[0026] In addition, in this invention, molding properties are sometimes also referred to as compression molding properties.

[0027] In the optical element of the present invention, the compressive stress of the compressive stress layer is preferably 100 MPa or more, more preferably 200 MPa or more, even more preferably 280 MPa or more, and most preferably 340 MPa or more. The greater the compressive stress, the higher the mechanical strength of the tempered glass.

[0028] On the other hand, when a very large compressive stress is formed on the surface, the tensile stress CT present in the tempered glass becomes high, posing a risk of natural damage. Therefore, the upper limit of the compressive stress of the compressive stress layer is preferably 1000 MPa or less, more preferably 800 MPa or less, even more preferably 650 MPa or less, and most preferably 600 MPa or less.

[0029] The depth of the compressive stress layer is such that the greater the depth, the more difficult it is for surface damage to penetrate the compressive stress layer, thus improving fracture resistance. Therefore, its lower limit is preferably 10 μm or more, more preferably 15 μm or more, and most preferably 20 μm or more. On the other hand, the greater the depth of the compressive stress layer, the higher the tensile stress CT present in the tempered glass, which poses a risk of natural damage and affects the refractive index and Abbe number, making it difficult to use as an optical element. Therefore, the upper limit of the depth of the compressive stress layer is preferably 100 μm or less, more preferably 70 μm or less, even more preferably 50 μm or less, further preferably 40 μm or less, and most preferably 33 μm or less.

[0030] The ratio of compressive stress to thermal stress (compressive stress / thermal stress) is preferably 1.00 or higher. This results in high thermal shock resistance, making it difficult for the optical element to break even with a large temperature difference. Therefore, the lower limit is preferably 1.00 or higher, more preferably 1.60 or higher, even more preferably 2.00 or higher, further preferably 2.20 or higher, and most preferably 2.40 or higher.

[0031] The thermal stress referred to here is expressed as the temperature difference when the temperature drops from 300°C to 100°C.

[0032] Thermal stress (MPa) = Young's modulus (10 8Pa) × Average linear thermal expansion coefficient α(10) -7 / ℃)×200(℃)×10-6

[0033] The optical element of the present invention can avoid thermal cracking due to its low thermal stress. Therefore, the upper limit of the thermal stress is preferably 330 MPa or less, more preferably 230 MPa or less, and even more preferably 180 MPa or less.

[0034] The optical element of the present invention can have a relatively small Young's modulus. Specifically, the upper limit of the Young's modulus of the optical element of the present invention is preferably 1100 (10⁻⁶). 8 Pa) or less, more preferably 1000 (10) 8 Pa) or less, more preferably 950 (10 Pa) or less, and even more preferably 950 (10 Pa) or less. 8 Pa) and below.

[0035] In the optical element of the present invention, the average linear thermal expansion coefficient α at 100–300°C is preferably 40–150 (×10⁻⁶). -7 The optical glass of the present invention, having an α value within the aforementioned range (°C), does not lose its thermal shock resistance and exhibits good expansion matching with the mold during precision pressing. More preferably, this α is 40–150 (×10⁻⁶). -7 / ℃), and more preferably 50~135 (×10)℃. -7 / ℃), more preferably 60~115 (×10)℃. -7 (°C), particularly preferably 65–105 (×10) -7 / ℃).

[0036] The optical element of the present invention preferably has a temperature of less than 700°C when logη = 8.5 (viscosity). This allows the glass to soften at a lower temperature, thus enabling pressing and molding of the glass at a lower temperature, and consequently, the pressing and molding of aspherical lenses with complex shapes. Furthermore, it reduces oxidation of the mold used in the pressing and molding process, and extends the mold's lifespan. Therefore, this temperature is preferably less than 700°C, more preferably less than 650°C, further preferably less than 620°C, and even more preferably less than 610°C.

[0037] The optical element of the present invention has a specified refractive index and an Abbe number within a specified range.

[0038] The refractive index (nd) of the optical element of the present invention is preferably 1.45000 or more at the lower limit, more preferably 1.48000 or more at the higher limit. The refractive index is preferably 1.70000 or less at the upper limit, more preferably 1.65000 or less at the lower limit, even more preferably 1.60000 or less at the lower limit, and even more preferably 1.55000 or less at the lower limit.

[0039] The Abbe number (νd) of the optical element of the present invention is preferably 45.00 or more at the lower limit, more preferably 47.00 or more, and even more preferably 50.00 or more. The upper limit of the Abbe number is preferably 70.00 or less, more preferably 67.00 or less.

[0040] The optical element of the present invention, having such a refractive index and Abbe number, is useful in optical design, especially in achieving high imaging characteristics and miniaturization of optical systems, thus increasing the degree of freedom in optical design.

[0041] The glass constituting the optical element of the present invention will now be described.

[0042] [Glass Composition]

[0043] In this specification, unless otherwise specified, the content of each component is expressed as cation % or anion % based on molar ratio. First, the components of the glass are distinguished as cationic and anionic components. Then, "cation %" is the percentage of each cationic component when the total content of all cationic components in the glass is expressed as 100 mol%. "anion %" is the percentage of each anionic component when the total content of all anionic components in the glass is expressed as 100 mol%.

[0044] <Regarding essential ingredients and optional ingredients>

[0045] Si 4+ It is a component that can promote stable glass formation, lower the liquidus temperature, and reduce devitrification (the formation of crystals).

[0046] In particular, by making Si 4+ With a Si content of 37.0% or higher, vitrification becomes easier, the coefficient of thermal expansion is reduced, and thermal shock resistance is increased. This not only yields glasses with excellent devitrification resistance but also improves ion substitution properties and tends to increase compressive stress. Therefore, Si... 4+ The content of [the substance] is preferably 37.0% or more, more preferably 41.0% or more, even more preferably 44.0% or more, and even more preferably 45.5% or more.

[0047] On the other hand, by making Si 4+ When the Si content is below 75.0%, meltability and formability tend to decrease, but this also helps prevent the coefficient of thermal expansion from becoming too low. Therefore, Si 4+ The content of [the substance] is preferably 75.0% or less, more preferably 70.0% or less, and even more preferably 67.5% or less.

[0048] Si4+ It can use SiO2, K2SiF6, Na2SiF6 and other materials as raw materials.

[0049] Li + Li is an ion-substituted component, and it is any component that can reduce high-temperature viscosity, improve melt flow and formability, and increase Young's modulus. Therefore, Li + The content of [the substance] is preferably 0% or more, more preferably greater than 0%, even more preferably 5.0% or more, even more preferably 10.0% or more, and most preferably 12.0% or more.

[0050] On the other hand, when Li + When the content is very high, there is a tendency for compressive stress to decrease. Low-temperature viscosity decreases, making stress relaxation more likely and compressive stress lower. An excessively high coefficient of thermal expansion reduces thermal shock resistance and makes it difficult to integrate with the thermal expansion coefficients of surrounding materials.

[0051] Therefore, Li + The content of [the substance] is preferably 30.0% or less, more preferably 26.0% or less, and even more preferably 24.0% or less.

[0052] Li + It can use Li2CO3, LiNO3, LiF and other raw materials.

[0053] Na + Na is an ion-substituted component and can be any component that can increase compressive stress, reduce high-temperature viscosity, improve meltability and formability, and increase the coefficient of thermal expansion. Therefore, Na + The content of [the substance] is preferably 0% or more, more preferably 0.1% or more, and even more preferably 0.2% or more.

[0054] On the other hand, by making Na + The content is below 25.0%, which can reduce the devitrification caused by excessive content.

[0055] Therefore, Na + The content of [the substance] is preferably 25.0% or less, more preferably 12.5% ​​or less, and even more preferably 10.0% or less.

[0056] Na + It can use Na2CO3, NaNO3, NaF, Na2SiF6, etc. as raw materials.

[0057] K + It is a component that promotes ion substitution and, in alkali metal oxides, readily increases the depth of the compressive stress layer. Furthermore, it reduces high-temperature viscosity, improves melt flowability and formability, and enhances resistance to devitrification. Therefore, K...+ The content of [the substance] is preferably 0% or more, more preferably greater than 0%, even more preferably 1.0% or more, and most preferably 3.0% or more.

[0058] On the other hand, when K + When the content of K is too high, the coefficient of thermal expansion will be too high, and the thermal shock resistance will be reduced. Therefore, K + The content of [the substance] is preferably 18.0% or less, more preferably 15.0% or less, and even more preferably 13.0% or less.

[0059] K + It can use K2CO3, KNO3, KF, KHF2, K2SiF6 and other raw materials.

[0060] B 3+ It is any component, and when its content is greater than 0%, it can promote stable glass formation and lower the liquidus temperature. Therefore, it can improve devitrification resistance, increase the solubility of glass raw materials, and enhance the strength, crack resistance, and other mechanical properties of the glass. Therefore, B 3+ The content of [the substance] is preferably 0% or more, more preferably greater than 0%, even more preferably 5.0% or more, further preferably 10.0% or more, even more preferably 13.0% or more, and most preferably 15.0% or more.

[0061] On the other hand, when B 3+ Over time, this can lead to decreased chemical durability and phase separation. Therefore, B 3+ The content of the component is preferably 35.0% or less, more preferably 30.0% or less, even more preferably 27.0% or less, and most preferably 25.0% or less.

[0062] B 3+ It can use H3BO3, Na2B4O7, Na2B4O7·10H2O, BPO4 and other raw materials.

[0063] Zn 2+ It is any component that can reduce viscosity at high temperatures. However, when Zn 2+ When the content of Zn is too high, the glass will undergo phase separation, its devitrification resistance will decrease, the depth of the compressive stress layer will become smaller, further increasing the likelihood of stress relaxation and reducing compressive stress. Therefore, Zn 2+ The content of [the substance] is preferably 0% or more, more preferably greater than 0%, even more preferably 0.1% or more, and even more preferably 0.2% or more.

[0064] On the other hand, by making Zn 2+ A Zn content of less than 2.0% can suppress glass phase separation, reduce devitrification resistance, and prevent the reduction of compressive stress caused by stress relaxation. Therefore, Zn2+ The content of the component is preferably 2.0% or less, more preferably 1.5% or less, even more preferably 1.0% or less, and most preferably 0.8% or less.

[0065] Nb 5+ and La 3+ Gd 3+ Y 3+ Yb 3+ Rare earth oxides are any component that can improve rigidity. However, the raw materials themselves are expensive, and when added in large quantities, the resistance to devitrification can easily decrease. Therefore, the content of rare earth oxides is preferably below 3%, more preferably below 2%, even more preferably below 1%, further preferably below 0.5%, and even more preferably below 0.1%.

[0066] Nb 5+ La 3+ Gd 3+ Y 3+ and Yb 3+ It can use Nb2O5, La2O3, La(NO3)3·XH2O (X is any integer), Y2O3, YF3, Gd2O3, GdF3, Yb2O3 and other raw materials.

[0067] Ti 4+ Ti is any component that can improve ion substitution performance and reduce high-temperature viscosity. Therefore, Ti 4+ The content of [specific ingredient] is preferably greater than 0%, more preferably greater than 0.02%, and most preferably greater than 0.03%.

[0068] On the other hand, by making Ti 4+ A concentration below 10.0% can reduce glass coloration and improve internal transmittance. Therefore, Ti... 4+ The content of [the substance] is preferably 10.0% or less, more preferably 5.0% or less, and even more preferably 1.0% or less.

[0069] Ti 4+ TiO2 and other materials can be used as raw materials.

[0070] Al 3+ It is any component that can improve ion replacement performance. When Al 3+ When the amount is too small, the ion substitution performance cannot be fully utilized. Therefore, Al 3+ The content of [specific ingredient] is preferably greater than 0%, more preferably 1.0% or more, even more preferably 1.5% or more, and most preferably 2.0% or more.

[0071] On the other hand, by making Al 3+The content is below 10.0%, which can reduce Al 3+ Excessive Al content leads to devitrification. 3+ The content of [the substance] is preferably 10.0% or less, more preferably 5.0% or less, and even more preferably 3.0% or less.

[0072] Al 3+ It can use Al2O3, Al(OH)3, AlF3 and other raw materials.

[0073] Mg 2+ It can be any composition, and it can lower the melting temperature of glass, reduce high-temperature viscosity, improve meltability, and increase Young's modulus.

[0074] On the other hand, by making Mg 2+ When the content of Mg is below 10.0%, the decrease in refractive index can be suppressed, thus reducing devitrification. Therefore, Mg 2+ The content of [the substance] is preferably 10.0% or less, more preferably 5.0% or less, and even more preferably 1.0% or less.

[0075] Mg 2+ It can use MgO, MgCO3, MgF2, etc. as raw materials.

[0076] Ca 2+ It can be of any composition, and it can reduce high-temperature viscosity, improve melt flow, and increase Young's modulus without reducing devitrification resistance. However, when Ca... 2+ When the content of Ca is too high, the density and coefficient of thermal expansion will increase. Furthermore, the glass composition will lack balance, making it prone to devitrification and reducing ion-exchange performance. There is also a tendency for ion-exchange solutions to deteriorate. Therefore, Ca... 2+ The content of the component is preferably 10.0% or less, more preferably 5.0% or less, even more preferably 3.0% or less, and most preferably 1.0% or less.

[0077] Ca 2+ It can use CaCO3, CaF2, etc. as raw materials.

[0078] Sr 2+ It can be any composition, and it can lower the melting temperature of glass, reduce high-temperature viscosity, improve meltability, and increase Young's modulus.

[0079] On the other hand, by making Sr 2+ When the content of Sr is below 10.0%, the glass will be stable and its devitrification can be suppressed. Therefore, Sr 2+ The content of [the substance] is preferably 10.0% or less, more preferably 5.0% or less, and even more preferably 1.0% or less.

[0080] Sr 2+ It can use Sr(NO3)2, SrF2 and other raw materials.

[0081] Ba 2+ It can be any component, and when its content is greater than 0%, it can reduce high-temperature viscosity and improve meltability and formability.

[0082] On the other hand, by making Ba 2+ With a content below 20.0%, devitrification during reheating and pressing can be reduced, and it is less likely to hinder ion substitution reactions. Therefore, Ba 2+ The content of [the substance] is preferably 20.0% or less, more preferably 15.0% or less, and even more preferably 12.0% or less.

[0083] Ba 2+ It can use BaCO3, Ba(NO3)2, etc. as raw materials.

[0084] Rn + (where Rn) + From Li + Na + K + One or more of the selected components from the group constitutes an arbitrary composition, and when the sum of their contents (by mass) is 5.0% or more, it can improve melt flowability and formability. Therefore, Rn + The lower limit of the sum is preferably 5.0% or more, more preferably 15.0% or more, and even more preferably 20.0% or more.

[0085] On the other hand, by making Rn + The sum of the contents (by mass) is 35.0% or less, which can suppress the decrease in refractive index and reduce devitrification caused by excessive content. Therefore, its upper limit is preferably 35.0% or less, more preferably 32.0% or less, and even more preferably 30.0% or less.

[0086] Zr 4+ It can be any component, and when the content is greater than 0%, it can increase the refractive index and Abbe number of glass.

[0087] On the other hand, by making Zr 4+ With a Zr content of 10.0% or less, devitrification can be reduced, and more homogeneous glass can be easily obtained. Therefore, Zr 4+ The content of [the substance] is preferably 10.0% or less, more preferably 5.0% or less, and even more preferably 1.0% or less.

[0088] Zr 4+ It can use ZrO2, ZrF4 and other materials as raw materials.

[0089] Ta 5+ It can be any component, and when the content is greater than 0%, it can increase the refractive index and the Abbe number.

[0090] On the other hand, by making Ta 5+ The content is below 10.0%, which can reduce Ta 5+ Excessive Ta content leads to devitrification. 5+ The content of [the substance] is preferably 10.0% or less, more preferably 5.0% or less, even more preferably 3.0% or less, and even more preferably 1.0% or less.

[0091] Ta 5+ It can use Ta2O5 and other materials as raw materials.

[0092] W 6+ It can be any composition, and when the content is greater than 0%, it can increase the refractive index and reduce the Abbe number, and can also improve the solubility of glass raw materials.

[0093] On the other hand, by making W 6+ When the content of W is below 10.0%, it can reduce the coloration of glass and suppress its devitrification. Therefore, W 6+ The content of [the substance] is preferably 10.0% or less, more preferably 5.0% or less, even more preferably 3.0% or less, and even more preferably 1.0% or less.

[0094] W 6+ It can use WO3 and other materials as raw materials.

[0095] P 5+ It can be any composition, and when the content is greater than 0%, it can improve the stability of glass, improve the ion replacement performance, and increase the depth of the compressive stress layer.

[0096] On the other hand, by making P 5+ The content is below 10.0%, which can reduce P. 5+ Excessive content leading to devitrification can prevent phase separation in the glass and inhibit the reduction of water resistance. Therefore, P 5+ The content of [the substance] is preferably 10.0% or less, more preferably 5.0% or less, and even more preferably 3.0% or less.

[0097] P 5+ It can use Al(PO3)3, Ca(PO3)2, Ba(PO3)2, BPO4, H3PO4 and other raw materials.

[0098] Ge 4+ It can be any component, and when the content is greater than 0%, it can increase the refractive index.

[0099] On the other hand, by making Ge 4+ When the content is below 10.0%, deosmosis can be suppressed. Therefore, Ge 4+ The content of [the substance] is preferably 10.0% or less, more preferably 5.0% or less, and even more preferably 3.0% or less.

[0100] Ge 4+ It can use GeO2 and other materials as raw materials.

[0101] Sn 4+ It can be any component, and when the content is greater than 0%, it can clarify (defoam) the molten glass and improve the ion replacement performance.

[0102] On the other hand, by making Sn 4+ With a content of less than 1.0%, it can prevent the formation of glass coloration and devitrification caused by the reduction of molten glass. Furthermore, it can reduce Sn... 4+ Alloying with melting equipment (especially precious metals such as Pt) can extend the lifespan of the melting equipment. Therefore, Sn 4+ The content of [the substance] is preferably 1.0% or less, more preferably 0.5% or less, and even more preferably 0.1% or less.

[0103] Sn 4+ It can use SnO, SnO2, SnF2, SnF4 and other materials as raw materials.

[0104] Sb 3+ Any component of the optical glass of this invention, when its content is greater than 0%, can promote defoaming of the glass, resulting in clear glass. By making Sb... 3+ A content of less than 1.0% relative to the total mass of glass makes excessive foaming during glass melting difficult and reduces the amount of Sb. 3+ It is difficult to alloy with melting equipment (especially precious metals such as Pt). Therefore, Sb 3+ The content of [the substance] is preferably below 1.0%, more preferably below 0.8%, and even more preferably below 0.6%.

[0105] Sb 3+ It can use Sb2O3, Sb2O5, Na2H2Sb2O7, 5H2O and other raw materials.

[0106] It should be noted that the components that clarify and defoam the glass are not limited to Sb mentioned above. 3+ The ingredients can include clarifying agents, defoamers, or combinations thereof known in the glass manufacturing industry.

[0107] F- When the content is greater than 0%, it has the property of making the glass difficult to devitrify.

[0108] On the other hand, F - When the content is too high, it will excessively increase the Abbe number of the glass, which will reduce the refractive index and lower the liquidus temperature. Therefore, F - The content of [the substance] is preferably 10.0% or less, more preferably 7.0% or less, and even more preferably 5.0% or less.

[0109] F - For example, fluorides with various cationic components such as AlF3, MgF2, and BaF2 can be used as raw materials to contain them in glass.

[0110] <Regarding ingredients that should not be present>

[0111] Next, the components that the optical glass of the present invention should not contain, and the components that are preferably not contained, will be described.

[0112] Other components can be added as needed without impairing the properties of the glass of the present invention. However, in addition to Ti, Zr, Nb, W, La, Gd, Y, Yb, and Lu, various transition metal components such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo have the property that, whether contained individually or in a composite form, even in small amounts, they will still color the glass and absorb light of specific wavelengths in the visible light region. Therefore, it is preferable to contain them substantially, especially in optical glass that uses wavelengths in the visible light region.

[0113] Additionally, Pb 2+ Lead compounds and As 3+ Arsenic compounds, being components with a high environmental burden, are preferably substantially absent, meaning they are completely absent except for unavoidable contamination.

[0114] Furthermore, Th, Cd, Tl, Os, Be, and Se have been increasingly avoided in recent years due to their status as hazardous chemicals. Environmental countermeasures are necessary not only in glass manufacturing but also in processing and post-production waste disposal. Therefore, given the importance of environmental impact, it is preferable to have these components substantially absent.

[0115] [Manufacturing Method]

[0116] The optical glass used in this invention can be manufactured, for example, as follows: The above-mentioned raw materials are uniformly mixed so that each component is within a specified content range. The mixture is then roughly melted in a platinum crucible, quartz crucible, or alumina crucible, and then placed in a gold crucible, platinum crucible, platinum alloy crucible, or iridium crucible. The mixture is melted at a temperature of 1000–1400°C for 3–5 hours, stirred to homogenize, and defoamed. The temperature is then lowered to 950–1250°C for fine stirring to remove texture. The glass is then cast into a mold and allowed to cool slowly, thus completing the manufacturing process.

[0117] [Optical Components]

[0118] Optical glass can be used to manufacture glass optical elements, for example, by molding. That is, a preform for molding can be made from optical glass, and the preform can be molded to produce a glass molded body. Alternatively, a preform made by grinding can be molded to produce a glass optical element. Furthermore, the methods for manufacturing the glass molded body are not limited to those described above.

[0119] Optical elements manufactured in this way are particularly preferably used for applications such as lenses and prisms. This reduces color blurring caused by chromatic aberration in the transmitted light of an optical system in which the optical element is installed. Therefore, when this optical element is used in a camera, it can more accurately represent the photographic subject; and when it is used in a projector, it can project the desired image more clearly.

[0120] The chemical strengthening method for optical elements of the present invention involves introducing alkali ions with large ionic radii onto the surface of the glass through ion replacement treatment at a temperature below the strain point of the glass. If a compressive stress layer is formed by chemical strengthening, a suitable compressive stress layer can be formed even with a thin glass sheet. Furthermore, after the compressive stress layer is formed, the strengthened glass is less prone to damage even when cut, unlike physical strengthening methods such as air-cooling strengthening.

[0121] Chemical strengthening methods can be implemented, for example, by contacting or impregnating a crystallized glass substrate with a molten salt containing potassium or sodium, such as potassium nitrate (KNO3), sodium nitrate (NaNO3), or a mixture or composite salt thereof. This contact or impregnation treatment with the molten salt (chemical strengthening treatment) can be carried out in one stage or in two stages.

[0122] For example, in the case of a one-stage chemical strengthening treatment, the patient is contacted or impregnated in a potassium or sodium salt, or a mixture thereof, heated to 350°C to 550°C for 30 minutes to 24 hours. In the case of a two-stage chemical strengthening treatment, in the first stage, the patient is contacted or impregnated in a sodium salt or a mixture of potassium and sodium salt, heated to 350°C to 550°C for 30 minutes to 24 hours. Then, in the second stage, the patient is contacted or impregnated in a potassium salt or a mixture of potassium and sodium salt, heated to 350°C to 550°C for 30 minutes to 24 hours.

[0123] Example

[0124] Table 1 shows examples of glass composition (a-c) used in this embodiment and comparative examples. It should be noted that the following embodiments are merely illustrative and are not limited to these embodiments.

[0125] The glass in Table 1 uses high-purity raw materials, such as oxides, hydroxides, carbonates, nitrates, fluorides, and metaphosphates, as the raw materials for each component. These raw materials are weighed and mixed uniformly in the proportions shown in Table 1, and then placed into a stone crucible (a platinum crucible or alumina crucible may also be used depending on the melting properties of the glass). Depending on the ease of melting the glass composition, the mixture is melted in an electric furnace at a temperature range of 1100–1400°C for 0.5–5 hours. After melting, the mixture is transferred to a platinum crucible for stirring, homogenization, and defoaming. The temperature is then lowered to 1000–1200°C, and after stirring and homogenization, it is cast into a mold and slowly cooled to produce the glass.

[0126] Table 1

[0127]

[0128] The refractive index (nd) and Abbe number (νd) of the glass in Table 2 were measured according to the V-block method specified in JIS B 7071-2:2018.

[0129] The photoelastic constant in Table 2 is determined by grinding the sample into a circular plate with a diameter of 25 mm and a thickness of 8 mm. A compressive load of 0 to approximately 100 kgf is applied along the side, and the optical path difference at a wavelength of 546.1 nm generated at the center of the glass is measured. The optical path difference is then calculated using the formula δ = β·d·F. In the above formula, the optical path difference is represented by δ (nm), the glass thickness by d (cm), and the stress by F (MPa).

[0130] The photoelastic constant is used to determine the compressive stress and depth of the compressive stress layer on a surface.

[0131] The average linear thermal expansion coefficient α (100-300℃) of the glass in Table 2 was obtained by measuring the relationship between the measurement temperature and the elongation of the sample in accordance with the Japanese Optical Glass Industry Standard JOGIS08-2003 "Method for Determination of Thermal Expansion of Optical Glass". The thermal expansion curve was obtained by measuring the relationship between the measurement temperature and the elongation of the sample, and the result was obtained from the thermal expansion curve.

[0132] The Young's modulus in Table 2 was determined in accordance with the test method for elastic modulus of fine ceramics specified in JIS R 1602:1995.

[0133] The temperature at which logη = 8.5 (viscosity) is given in Table 2. The glass sample was processed into a sample shape of approximately φ7×7mm and the glass sample was processed into a parallel plane. The viscosity was measured using a glass parallel plate viscosity measuring device (model: PPVM-1100).

[0134] Table 2

[0135]

[0136] Each sample (a-c) was cut and ground, and then double-sided parallel grinding was performed to make a thickness of about 1.0 mm to produce a glass plate.

[0137] Next, the fabricated glass plates were chemically strengthened according to the conditions in Tables 3 to 5. Based on the number and spacing of interference fringes observed using a surface stress meter (Orihara Manufacturing Co., Ltd.'s FSM-6000LE), the compressive stress and depth of the compressive stress layer on the surface were calculated. The refractive index (nd) and the measured optical elastic constant (β) of each sample were used in the calculations.

[0138] Table 3 shows examples and comparative examples of sample a that underwent chemical fortification treatment.

[0139] Table 3

[0140]

[0141] Table 4 shows examples and comparative examples of sample b that underwent chemical fortification treatment.

[0142] Table 4

[0143]

[0144] Table 5 shows an example of sample c that underwent chemical fortification treatment.

[0145] Table 5

[0146]

[0147] As shown in Table 2, the temperature at which the logη (viscosity) of the samples (a-c) used in this embodiment and the comparative example reaches 8.5 is less than 700°C. Therefore, it can be seen that the samples (a-c) used in this embodiment and the comparative example have excellent compressibility.

[0148] In addition, for the samples (a-c), the refractive index (nd) of any one of them is above 1.45000 and below 1.70000, and the Abbe number (νd) is above 45.00 and below 70.00, which is within the required range.

[0149] The compressive stresses of the embodiments shown in Tables 3 to 5 are 100–1000 MPa, and the depth of the compressive stress layer is 10–100 μm, which are within the desired range. Comparative Example b-1 shown in Table 4 has a compressive stress layer depth of only 9.7 μm, which is outside the desired range.

[0150] As shown in Tables 3 to 5, the compressive stress / thermal stress ratio of the embodiments is above 1.00. Therefore, the embodiments shown in Tables 3 to 5 have good thermal shock resistance.

[0151] While the present invention has been described in detail above for illustrative purposes, the present embodiments are merely illustrative and should be fully understood by those skilled in the art to make many modifications to the present invention without departing from the spirit and scope thereof.

Claims

1. An optical element having a compressive stress layer on its surface, wherein, The glass constituting the optical element, in terms of cations (mol%): Si 4+ The content is between 41.0% and 75.0%. Rn + The sum of the contents is between 20.0% and 35.0%, where Rn + From Li + Na + K + One or more of the groups constituted, Al 3+ The content is below 6.40%. Zn 2+ The content is less than 1.0%. Mg 2+ The content is less than 1.0%. Ca 2+ The content is less than 1.0%. Sr 2+ The content is less than 1.0%. Ba 2+ The content is less than 0.51%, and B 3+ The content is above 15.0% and below 20.83%, and Fe-free The compressive stress of the compressive stress layer is 100–1000 MPa, and the depth of the compressive stress layer is 10–100 μm. The temperature at which the viscosity satisfies logη = 8.5 is less than 700℃.

2. The optical element as claimed in claim 1, wherein, The refractive index (nd) is between 1.45000 and 1.70000, and the Abbe number (νd) is between 45.00 and 70.

00.

3. The optical element as described in claim 1 or 2, wherein, The ratio of compressive stress to thermal stress, i.e., compressive stress / thermal stress, is greater than 1.

00.

4. The optical element as described in any one of claims 1 to 3, wherein, This optical element can be used in projection optical system equipment.

5. The optical element as described in any one of claims 1 to 3, wherein, This optical element can be used in photographic optical system equipment.

Citation Information

Patent Citations

  • Ultraviolet screening filter

    JP1983049636A

  • Glass for press molding and substrate glass for information recording medium

    JP2002211946A

  • Glass and chemically tempered glass

    JP2012211083A

  • Alkali aluminosilicate glass for 3D precision molding and thermal bending.

    JP2013528561A

  • Optical glass

    JP2019006643A